1997
DOI: 10.1038/sj.onc.1201404
|View full text |Cite
|
Sign up to set email alerts
|

DNA-damage-inducible p53 activity in SV40-transformed cells

Abstract: The biological state of the tumour suppressor proteins Rb and p53 is altered in papillomavirus-and SV40-transformed cells, due to interaction with the DNA tumour virus oncogene proteins E6/E7 and the tumour (T) antigen. Thus, the DNA damage response function of p53, a crucial feature of the tumour suppressor p53, might be considered as inactive. To investigate this subject, C57SV and VLM, two SV40-transformed murine cell lines enharboring constitutively high nuclear p53 and SV40 large T antigen levels, were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…on May 10, 2018 by guest http://mcb.asm.org/ achieve near saturation of p53), with early reports that expression of exogenous mutant p53 could enhance transformation by T (42), and finally with a recent report of residual DNA damage-inducible p53 activity in SV40-transformed murine cell lines (30). Direct evidence for this notion comes from immunofluorescence analysis of the behavior in our model of a key downstream target of p53, p21…”
Section: Discussionmentioning
confidence: 72%
“…on May 10, 2018 by guest http://mcb.asm.org/ achieve near saturation of p53), with early reports that expression of exogenous mutant p53 could enhance transformation by T (42), and finally with a recent report of residual DNA damage-inducible p53 activity in SV40-transformed murine cell lines (30). Direct evidence for this notion comes from immunofluorescence analysis of the behavior in our model of a key downstream target of p53, p21…”
Section: Discussionmentioning
confidence: 72%
“…Both GM637 and GM5849 cells are transformed by the SV40 virus and express SV40Tag. SV40 Tag protein binds to and stabilizes p53, resulting in elevated levels of p53 (Hess and Brandner, 1997;Kohli and Jorgensen, 1999;. Changes in p53 protein levels after DNA damage are therefore not usually detected in SV40-transformed cells (Kohli and Jorgensen, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The human lens epithelial cell line used in this study is immortalized from primary cultures through transfection with a plasmid containing the gene encoding simian virus 40 large-T antigen (SV40-TAg) (Ibaraki et al, 1998). Although SV40-TAg is well known to interact with tumor suppressor proteins p53 and RB, and therefore may disable their normal cellular signaling pathways in immortalized cells (Chen et al, 1992;Bryan and Reddel, 1994), a number of recent studies have demonstrated that, in SV40-Tag-transformed murine and human cells, p53 is still functional in responses to DNA damage (Hess and Brandner, 1997;Kohli and Jorgensen, 1999). Our present study also reveals that p53 and Rb are not completely inactivated by SV40-TAg in HLE cells.…”
mentioning
confidence: 99%